2014
DOI: 10.1364/ol.39.001713
|View full text |Cite
|
Sign up to set email alerts
|

Difference of cross-spectral densities

Abstract: Generally speaking, the difference between two cross-spectral densities (CSDs) does not represent a correlation function. We will furnish a sufficient condition so that such difference be a valid CSD. Using such a condition, we will show through some examples how new classes of CSDs can be generated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Equations (8) and (9) are slightly more general distributions than given in [6], the difference accounting for anisotropy of correlation functions along x and y directions. In order for ( ) p v to be nonnegative [13,14] it suffices to set and .…”
Section: Optical Frames With Polar Symmetrymentioning
confidence: 99%
“…Equations (8) and (9) are slightly more general distributions than given in [6], the difference accounting for anisotropy of correlation functions along x and y directions. In order for ( ) p v to be nonnegative [13,14] it suffices to set and .…”
Section: Optical Frames With Polar Symmetrymentioning
confidence: 99%
“…Furthermore, a recent study has confirmed the fact that the difference between the two CSDs is a genuine CSD if there exists a kernel with respect to which two CSDs W 0 1 and W 0 2 belong to the same class and have weight functions p 1 v and p 2 v satisfying the inequality p 1 ≥ p 2 for any v [11]. The function pv can be written as the difference between two nonnegative functions p 1 v and p 2 v such that…”
mentioning
confidence: 90%
“…In this Letter, we first introduce another partially coherent source class with a non-Gaussian Schell-model, which has a sinc Schell-model (SSM) correlation source, taken from a recent theory developed for analyzing the correlation sources and the fields that the sources generate [10]. And then, we construct the difference between two SSM sources to generate a new genuine spatial correlation source based on the propositions suggested recently by Santarsiero et al [11]. Two types of SSM sources have different coherence distributions which are found to lead to different intensity distributions of beams during propagation.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] It is also expected that interesting results could be found if the vectorial nature of light is taken into account. The coherence and polarization characteristics of a light source can be appropriately described by its cross-spectral density matrix (CSDM).…”
Section: Introductionmentioning
confidence: 99%